Analysis of Factors that Influence Taxpayers Compliance in Fulfilling Taxation Obligations - Ayu Fuady Sania; Ivan Yudianto (Universitas Padjadjaran, 2018)
This study aims to determine the factors that affect taxpayer compliance. This research uses taxpayer awareness, moral obligation, and quality of tax service as factors. A questionnaire was used as research instruments in data collection. Respondents in this research are e-Commerce business actor who uses an online marketplace. Multiple linear regression with SPSS program version 23 is used for data analysis. The results of this study concluded that taxpayer awareness, moral obligations, and the quality of tax service simultaneously influenced significantly to taxpayer compliance. Then the test partially produces the taxpayer awareness, and the quality of tax service has a positive and significant effect on taxpayer compliance, while the moral obligation has not a positive and significant effect on taxpayer compliance.